PERRANCANGAN METODE PEMBELAJARAN PENGENALAN KENDARAAN MENGGUNAKAN AUGMENTED REALITY PADA ANAK PAUDIT LHI YOGYAKARTA - I'tishom Amirul Haq, Muhammad Nur; Nugroho, Agung (Jurnal Teknologi Informasi, 2025)
This study aims to design an interactive learning medium using Augmented Reality (AR) to introduce public transportation to early childhood students at PAUDIT LHI Yogyakarta. The problem addressed is the low learning motivation caused by conventional media use. The proposed solution is an AR-based application that displays 3D vehicle objects, includes voice narration, and works offline. The research employed a quantitative approach with a quasi-experimental method. The application was developed using Unity and Vuforia, and tested through alpha and beta testing. Results showed the application functioned properly and received an "Excellent" rating with a score of 88.9% from teachers and students. In conclusion, the application effectively increased children’s interest, engagement, and understanding of public transportation, highlighting the potential of AR in early childhood education.KeyWords: Augmented Reality; Early Childhood Education; Learning Media; Public Transportation; Interactive Application